Microbiota alteration at different stages in gastric lesion progression: a population-based study in Linqu, China - Kadeerhan, Gaohaer; Gerhard, Markus; Gao, Juan-Juan; Mejías-Luque, Raquel; Zhang, Lian; Vieth, Michael; Ma, Jun-Ling; Bajbouj, Monther; Suchanek, Stepan; Liu, Wei-Dong; Ulm, Kurt; Quante, Michael; et al. (American journal of cancer research, 2021)
In addition to Helicobacter pylori (H.pylori), gastric microbiota may be involved in carcinogenesis process. However, the longitudinal study to assess changes in the gastric microbiota associated with the development of gastric carcinogenesis is still limited. The aim of this study is to explore dynamic microbial alterations in gastric cancer (GC) development based on a 4-year endoscopic follow-up cohort in Linqu County, China. Microbial alterations were investigated by deep sequencing of the microbial 16S ribosomal RNA gene in 179 subjects with various gastric lesions, and validated in paired gastric biopsies prospectively collected before and after lesion progression and in non-progression controls. Significant differences were found in microbial diversity and community structure across various gastric lesions, with 62 candidate differential taxa between at least two lesion groups. Further validations identified Helicobacter, Bacillus, Capnocytophaga and Prevotella to be associated with lesion progression-to-dysplasia (DYS)/GC (all P < 0.05), especially for subjects progressing from intestinal metaplasia (IM) to DYS/GC. The combination of the four genera in a microbial dysbiosis index showed a significant difference after lesion progression-to-DYS/GC compared to controls (P = 0.027). The panel including the four genera identified subjects after progression-to-DYS/GC with an area under the receiver-operating curve (AUC) of 0.941. Predictive significance was found before lesion progression-to-DYS/GC with an AUC = 0.776 and an even better AUC (0.927) for subjects progressing from IM to DYS/GC. Microbiota may play different roles at different stages in gastric carcinogenesis. A panel of bacterial genera associated with gastric lesions may help to assess gastric microbial dysbiosis and show potential predictive values for lesion progression. Our findings provide new clues for the microbial mechanism of H.pylori-associated carcinogenesis.
Keywords: lesion progression; Helicobacter pylori; dysbiosis; Gastric microbiota